Formation of Cardiopulmonary Resuscitation Teams: A Qualitative Content Analysis - Shirvani, Yadolah; Cheraghi, Mohammad Ali; Javadi-Pashaki, Nazila; Emami-Sigaroudi , Abdolhossein (Shahroud Journal of Medical Sciences, 2025)
Background: Cardiac arrest is a life-threatening condition where the outcome depends critically on immediate interventions through basic and advanced cardiopulmonary resuscitation. The quality of these interventions depends on the CPR team's performance, which itself is determined by how the team forms. Therefore, this study was conducted to understand cardiopulmonary CPR team members' experiences of team formation and its influencing factors. Methods: This qualitative study used conventional content analysis in Iran over a 14-month period (December 2023 to January 2025). The study population included all members of cardiopulmonary CPR teams at Guilan University of Medical Sciences-affiliated hospitals. We used purposive sampling and continued recruitment until data saturation was achieved after 18 interviews with 18 participants. Semi-structured interviews were conducted, and data were analyzed using MAXQDA 20. Results: Data analysis led to the identification 2 main categories — with 6 subcategories, including the membership method (mandatory membership, voluntary membership, incidental membership) and selection criteria (ability criteria, contractual criteria, no specific criteria). Conclusions: The composition of CPR teams ranges from volunteers and motivated individuals to those with mandatory membership, so that if the “membership method” of the members is voluntary and noncoercive and the selection of members is based on specific competency criteria, the team's performance is more likely to be effective.